2018
DOI: 10.1080/20009666.2018.1472514
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent spontaneous pneumothorax in pregnancy – a case report and review of literature

Abstract: Spontaneous pneumothorax in pregnancy is a rare and life-threatening condition. In this report, a case of spontaneous pneumothorax occurring at 34 weeks’ gestation in a healthy 34-year-old primigravida is described. She had typical complaints of chest pain and dyspnoea and diagnosis was made by chest X-ray which showed an extensive pneumothorax in the right side. Pneumothorax recurred twice over approximately three weeks. A caesarean section secondary to small pelvic parameters was scheduled with the chest tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 11 publications
2
18
0
4
Order By: Relevance
“…Review of the literature showed that most of the cases of pneumothorax occurred during the last trimester and during the perinatal period. 1,3,7 Pneumothorax in pregnancy presents with the same signs and symptoms as described in our case i.e., pleuritic chest pain and shortness of breath. 7 However, these symptoms are nonspecific and can be attributed to other more common diseases like asthma, paroxysmal tachycardia, or neuralgia.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Review of the literature showed that most of the cases of pneumothorax occurred during the last trimester and during the perinatal period. 1,3,7 Pneumothorax in pregnancy presents with the same signs and symptoms as described in our case i.e., pleuritic chest pain and shortness of breath. 7 However, these symptoms are nonspecific and can be attributed to other more common diseases like asthma, paroxysmal tachycardia, or neuralgia.…”
Section: Discussionsupporting
confidence: 74%
“…4 Various changes occurring in the respiratory physiology during pregnancy like a decrease in functional residual capacity and total lung capacity and an increase in respiratory rate, minute ventilation and tidal volume are responsible for the increased risk of pneumothorax in pregnancy. 3,5,6 In our case, both episodes of pneumothorax occurred during the same pregnancy in the last trimester. Review of the literature showed that most of the cases of pneumothorax occurred during the last trimester and during the perinatal period.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Thus labour entails a ‘perfect storm’ for barotrauma to unmask anatomical defects and rarely ensuing unilateral pneumothorax [6], pneumomediastinum (Hamman’s syndrome) [7], pneumopericardium [8], oesophageal perforation [9] and even diaphragmatic rupture [10] have all been described. In this case, signs of underlying pulmonary lymphangioleiomyomatosis were subsequently identified.…”
Section: Discussionmentioning
confidence: 99%